2016
DOI: 10.15430/jcp.2016.21.3.144
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory Activity of Mori folium, the Leaf of Morus alba L., in RAW 264.7 Macrophages In Vitro

Abstract: BackgroundImmunoregulatory elements have emerged as useful immunotherapeutic agents against cancer. In traditional medicine, Mori folium, the leaf of Morus alba L. (Moraceae), has been used for various medicinal purposes; however, the immunomodulatory effects have not been fully identified. We evaluated the immunoenhancing potential of water extract of Mori folium (WEMF) in murine RAW264.7 macrophages.MethodsRAW264.7 cells were treated with WEMF for 24 hours and cell viability was detected by an MTT method. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
1
17
0
2
Order By: Relevance
“…In group III (ALI+NaHS), iNOS expression was significantly increased in comparison with control group but significantly decreased in comparison with ALI group. However, administration of PAG (ALI+PAG) led to significant increase in iNOS expression in comparison with both control and ALI groups (Table 2) is an endotoxin found in the external membrane of gram negative bacteria and causes an intense inflammatory response in mammals (Kwon et al 2016). During the present study, LPS was given for induction of ALI in rats which was confirmed by histopathological examination.…”
Section: Immunohistochemical Assessment Of Inossupporting
confidence: 58%
“…In group III (ALI+NaHS), iNOS expression was significantly increased in comparison with control group but significantly decreased in comparison with ALI group. However, administration of PAG (ALI+PAG) led to significant increase in iNOS expression in comparison with both control and ALI groups (Table 2) is an endotoxin found in the external membrane of gram negative bacteria and causes an intense inflammatory response in mammals (Kwon et al 2016). During the present study, LPS was given for induction of ALI in rats which was confirmed by histopathological examination.…”
Section: Immunohistochemical Assessment Of Inossupporting
confidence: 58%
“…In traditional Chinese medicine, M. alba leaves have been used to treat fever and cold for thousands of years. It has been reported to exhibit various biological activities, including anti-inflammatory, neuroprotection, antioxidant, anti-Alzheimer’s, and anti-diabetic effects [ 8 , 9 , 10 , 11 , 12 ]. Recently, extracts from M. alba leaves have been shown to inhibit melanogenesis in mushroom tyrosinase activity assays [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The leaf of plant, Mori folium (Supplementary Material, Figure S1), has been used in traditional medicine for the treatment of various diseases (Yang et al 2014, Chan et al 2016). Mori folium exhibits a variety of pharmacological activities, such as anti-microbial (Tirupathi et al 2011), antitumor (Deepa et al 2013), anti-obesity (Sugimoto et al 2009, Ann et al 2015), anti-hypotensive (Kobayashi et al 2010, neuroprotective (Xiang et al 2010), anti-diabetic (Naowaboot et al 2009, and immunomodulatory potentials (Kwon et al 2016). In addition, Mori folium possesses free radical-scavenging activities (Kim and Jang 2011, Iqbal et al 2012, Raman et al 2016, which may explain its antioxidant ability (Khan et al 2013, Raman et al 2016.…”
Section: Introductionmentioning
confidence: 99%